PERUBAHAN TARI JATHILAN PADA KESENIAN REOG PONOROGO SINGO MANGGOLO MEKARSARI DI DESA TITIAN RESAK KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Nabilla Meilina Putri; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study examines the changes in the jathilan dance in the art of Reog Ponorogo Singo Manggolo Mekarsari. The purpose of this study was to determine: 1) Changes in the Jathilan dance in the Reog Ponorogo Singo Manggolo Mekarsari art. 2) The relationship between jathilan changes to the socio-economic conditions of Reog Ponorogo Singo Manggolo Mekarsari. This study used qualitative research methods. Theory used Talcott Parsons AGIL Theory. Data were collected through interviews, observation, and documentation. In this case, determining the informant using a purposive technique that has been determined previously. The informants of this research were seven people. The results of this study change the jathilan dance because there are social deviations and the inclusion of keyboard music. However, it did not appear from 1995 to 2007. This change in the Jathilan dance followed the adjustment of the Reog Ponorogo art group in Java. Changes that occur in clothing, music, songs, and movements. The change in the jathilan dance, which was originally male, has now changed to female. With strong cultural principles they do not mind the amount of wages they receive. On the other hand, the appearance of this art is so that it is always maintained and can preserve this art. Keywords: Change, Jathilan Dance, Reog Ponorogo